2022
DOI: 10.3174/ajnr.a7427
|View full text |Cite
|
Sign up to set email alerts
|

PET/MR Imaging in Evaluating Treatment Failure of Head and Neck Malignancies: A Neck Imaging Reporting and Data System–Based Study

Abstract: BACKGROUND AND PURPOSE: PET/MR imaging is a relatively new hybrid technology that holds great promise for the evaluation of head and neck cancer. The aim of this study was to assess the performance of simultaneous PET/MR imaging versus MR imaging in the evaluation of posttreatment head and neck malignancies, as determined by its ability to predict locoregional recurrence or progression after imaging. MATERIALS AND METHODS:The electronic medical records of patients who had posttreatment PET/MR imaging studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…107 Applying the NI-RADS criteria 16 to PET/MR imaging in a retrospective study including 46 patients, Patel and colleagues reported that PET/MR imaging scores showed a strong association with treatment failure for the primary site, neck lymph nodes, and combined sites, and the AUCs of PET/MR imaging scores versus treatment failure were 0.864 to 0.987, P < .001. 108 The investigators, therefore, concluded that PET/MR imaging has an excellent discriminatory performance for treatment outcomes of HNSCC when NI-RADS is applied.…”
Section: Evaluation Of Treatment Response and Detection Of Recurrent ...mentioning
confidence: 99%
“…107 Applying the NI-RADS criteria 16 to PET/MR imaging in a retrospective study including 46 patients, Patel and colleagues reported that PET/MR imaging scores showed a strong association with treatment failure for the primary site, neck lymph nodes, and combined sites, and the AUCs of PET/MR imaging scores versus treatment failure were 0.864 to 0.987, P < .001. 108 The investigators, therefore, concluded that PET/MR imaging has an excellent discriminatory performance for treatment outcomes of HNSCC when NI-RADS is applied.…”
Section: Evaluation Of Treatment Response and Detection Of Recurrent ...mentioning
confidence: 99%